Quantifying Extreme Values in Geomagnetic Perturbations Using Ground Magnetic Records - J. Rodríguez‐Zuluaga; J. Gjerloev; S. Ohtani; Y. Zou; B. Anderson (Space Weather)
Abstract We comprehensively analyzed geomagnetic perturbations using ground magnetic records from over 400 stations spanning four solar cycles, from 1976 to 2023. We assess the perturbations in the three magnetic components separately. Our study covers low, middle, and high magnetic latitudes in the northern magnetic hemisphere, with the primary objective of quantifying extreme values and evaluating their variability on magnetic latitude, local time, and solar cycle phases “minimum, ascending, maximum, and declining.” Our findings reveal spatial patterns to be less discernible as perturbations intensify, with distinct responses at middle and high latitudes. The extreme values, defined as percentiles 0 and 100, were observed to be localized and randomly distributed in local time, especially in the east magnetic component. Additionally, we observed dusk‐dawn asymmetries in the magnitude of perturbations related to the auroral electrojets, indicating complex interactions between the magnetosphere and ionosphere. Furthermore, the results reveal a preference for the most significant extreme values to occur in the declining phase of the solar cycle. These insights deepen our understanding of geomagnetic perturbations and their variability, contributing to space weather forecasting and mitigation strategies.